Acid-tolerant Bacteria from Plant Soils: Potential Role in Plant Growth Promotion - Iqbal, Muhammad Naeem; Ashraf, Asfa (International Journal of Molecular Microbiology, 2021)
Microbes play an important role in the plant-soil ecosystem as they promote better plant growth, inhibit plant pathogens and pests, help in the acquisition of minerals, and maintain the biogeochemical cycles. Acidic soils inhibit plant growth by continuously increasing acid in soils. Microorganisms support plant growth in several environmental conditions. There is a dearth of knowledge about the impact of increasing soil acidity on resident bacterial communities and their functionality in the plant soils. In this issue, Mohammad et al. isolate microbial strains from the soils which were found to resist acidic pH and regulate pH value of the acidic soil. There is potential to move forward with more sustainable agriculture based on knowledge at hand on acidic soils, and the role microbes can play in the agricultural management of acidity.